ChemInform Abstract: Six New Tin—Sulfur Containing Compounds Obtained under Solvothermal Conditions. Issue 34 (26th August 2014) - Pienack, Nicole; Luehmann, Henning; Seidlhofer, Beatrix; Ammermann, Janina; Zeisler, Christoph; Danker, Felix; Naether, Christian; Bensch, Wolfgang
Abstract The structures of the new tin—sulfur containing compounds are determined by XRD.